The Role of Mean Platelet Volume as a Predictor of Mortality in Critically Ill Patients: A Systematic Review and Meta-Analysis - Pattraporn Tajarernmuang; Arintaya Phrommintikul; Atikun Limsukon; Chaicharn Pothirat; Kaweesak Chittawatanarat (Critical Care Research and Practice)
Background. An increase in the mean platelet volume (MPV) has been proposed as a novel prognostic indicator in critically ill patients. Objective. We conducted a systematic review and meta-analysis to determine whether there is an association between MPV and mortality in critically ill patients. Methods. We did electronic search in Medline, Scopus, and Embase up to November 2015. Results. Eleven observational studies, involving 3724 patients, were included. The values of initial MPV in nonsurvivors and survivors were not different, with the mean difference with 95% confident interval (95% CI) being 0.17 (95% CI: −0.04, 0.38; p=0.112). However, after small sample studies were excluded in sensitivity analysis, the pooling mean difference of MPV was 0.32 (95% CI: 0.04, 0.60; p=0.03). In addition, the MPV was observed to be significantly higher in nonsurvivor groups after the third day of admission. On the subgroup analysis, although patient types (sepsis or mixed ICU) and study type (prospective or retrospective study) did not show any significant difference between groups, the difference of MPV was significantly difference on the unit which had mortality up to 30%. Conclusions. Initial values of MPV might not be used as a prognostic marker of mortality in critically ill patients. Subsequent values of MPV after the 3rd day and the lower mortality rate unit might be useful. However, the heterogeneity between studies is high.